(untitled) (Journal of Forensic Medicine & Toxicology, 2017)
Rupture of the uterus is a disruption in the continuity of all uterine layers any time beyond 28 weeks of pregnancy. Uterine rupture is a disastrous medical emergency. Many risk factors for uterine rupture have been identified. We hereby report the rare case of spontaneous rupture of the gravid uterus at 36 weeks of pregnancy in grand multipara, with obstetrics history as G5-P4-A0-L4. She had no complaints during her antenatal visits and also no aggravating factors were reported during investigations. The current case highlights the complications arising due to improper antenatal care. The judicious selection of at-risk mothers well in advance and mandatory hospital delivery would have prevented such life-threatening complication. The careful medicolegal examination in such maternal deaths will help by opining about the exact cause of death.